2016
DOI: 10.17645/si.v4i4.675
|View full text |Cite
|
Sign up to set email alerts
|

The 'Arc of Prosperity' Revisited: Homelessness Policy Change in North Western Europe

Abstract: This paper compares continuity and change in homelessness policy in Ireland, Scotland and Norway with a particular focus on the period of post-crisis austerity measures (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016). The analytical approach draws on institutional theory and the notion of path dependency, which has rarely been applied to comparative homelessness research. The paper compares welfare and housing systems in the three countries prior to presenting a detailed analysis of the conceptualisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…While there is a substantial research literature on the health of homeless people, homelessness itself also requires to be understood as a structural issue of lacking a suitable home [1618]. Research has shown that poor housing quality is associated with morbidity related to infectious and chronic diseases, injuries, poor nutrition, asthma, neurologic damage, and mental disorders [19].…”
Section: Introductionmentioning
confidence: 99%
“…While there is a substantial research literature on the health of homeless people, homelessness itself also requires to be understood as a structural issue of lacking a suitable home [1618]. Research has shown that poor housing quality is associated with morbidity related to infectious and chronic diseases, injuries, poor nutrition, asthma, neurologic damage, and mental disorders [19].…”
Section: Introductionmentioning
confidence: 99%
“…A concurrent, though often separate, debate in the homelessness literature is the benefits of adopting 'housing-led' approaches (ECCH, 2010;FEANTSA, 2011). Housing-led designates a broad range of policies and services that prioritise the provision of stable housing to homeless households as the first action to take (Anderson et al, 2016;EECH, 2010;O'Sullivan, 2008). While this can be through enforceable rights, it encompasses all approaches that "treat housing as a fundamental right and a prerequisite to solving [any] other problems" (EECH, 2010: 14) experienced by homeless households.…”
Section: Scotland's Right To Housingmentioning
confidence: 99%
“…Within international debates on the best response to homelessness there has been increasing attention given to both rights-based and housing-led approaches (Anderson, et al 2016;ECCH, 2010;FEANTSA, 2011 andFitzpatrick and Watts, 2010). Each has been promoted for increasing access to housing and empowering homeless people (Kenna, 2005;Ridgway and Zipple, 1990;Watts, 2013 and.…”
Section: Introductionmentioning
confidence: 99%
“…They tackle core conceptual issues such as defining and measuring homelessness (Anderson et al, 2016;Clarke, 2016); as well as the emerging challenges of understanding and responding to a wide and complex range of needs which homeless people may have, beyond a need for housing (Christian et al, 2016;Macías Balda, 2016;Quilgars & Pleace, 2016). Going forward, the monitoring and evaluation of the impacts of differing policy and practice responses to homelessness remains challenging albeit with some methodological progress identified (Christian et al, 2016;Quilgars & Pleace, 2016).…”
mentioning
confidence: 99%
“…A degree of resilience has been identified in the roles of institutions which tackle homelessness in different nations and their capacity to influence policy, even in face of severe economic crisis (Anderson et al, 2016). However, the comparative analysis of homelessness policy and its impacts within and across nation states remains a challenge for homelessness research with considerable scope for further cross-national and longitudinal research on understanding homelessness and evaluating policy responses.…”
mentioning
confidence: 99%